INTER-LABORATORY AND OTHER ERRORS IN PB ISOTOPE ANALYSES INVESTIGATED USING A 207PB-204PB DOUBLE SPIKE - Thirlwall M.F. (My University, 2000)
A method for precise Pb analysis using a 207Pb-204Pb spike has been developed at Royal Holloway. Pb isotope ratios are calculated relative to 206Pb and are normalised in a run to an arbitrary 208Pb/206Pb ratio to permit good estimates of error propagation through the fractionation correction. While 204Pb/206Pb normalised to 208Pb/206Pb appears free from interferences and obeys power- or exponential-law mass fractionation within analytical error, 207Pb/206Pb shows systematic decreases with increase in 208Pb/206Pb at >1250°C that are extremely difficult to explain by isobaric interference and may indicate abnormal mass fractionation behaviour. However, this behaviour is absent from plasma-source mass spectrometers. Correction for the effect improves external reproducibility of SRM981 from 96 to 82 ppm (1sd, 33 analyses over 1 year) for 206Pb/204Pb, and from 64 to 43 ppm for 207Pb/206Pb. For 206Pb/204Pb, this external reproducibility is only about twice the typical internal error on a single analysis after error propagation through the fractionation correction. Relative to the fractionation-corrected isotope ratios, measured ratios for unknown samples analysed are significantly more enriched in the lighter isotopes than are runs of SRM981, indicating that corrections based on average SRM981 mass fractionation are likely to be in error. Acid-leached rock chips and acid-leached powders generally give identical Pb ratios within analytical error. However, re-analysis of samples previously published by several laboratories shows large differences, up to 30x the supposed reproducibility of conventional Pb isotope determinations, probably related both to inadequate fractionation corrections and to environmental contamination of rock powder.
Keywords: LEAD ISOTOPES; ACCURACY; TIMS; ERRORS